How severely does violence deter international investment? - S. Brock Blomberg; Ashoka Mody (Claremont McKenna College, Department of Economics, 2005)
The relevance of political risk to international trade and investment remains a topic of continuing interest. However, summary measures of political risk, including country corruption, do not give consistent results. In this paper, we bring together two recent streams of literature to highlight the role of political risk. We find that violence in the form of terrorism, revolutions, and wars is harmful to international investment. Violence in a source country encourages investment away from the parent to a safer host. Host country violence hurts investment, mainly in developing countries. Developing countries also attract more investment through membership in the World Trade Organization (WTO). We interpret WTO membership as a commitment device that limits the possibility of arbitrary policy changes.
Keywords: E6; H1; H5; D74; O11; 330; FDI; Trade; Conflict; Terrorism